The politics of International Intervention and Conflict Management in contemporary political order: a lack of world Political Leadership - Shuriye, Abdi Omar (2006)
The UN is making repetitive diplomatic attempts through its resolutions to send peacekeeping force to the Sudanese region of Dafur, it has succeeded to send a large number of troops to Lebanon, and the AU struggles to concur on schema to send African forces to Somalia. NATO forces on the other side are engaged in fierce battles against Taliban fighters in the mountainous region of south Afghanistan, all under one name: international intervention. The fundamental aim of intervention is to lessen the consequences of conflict, usually in the form of violence and destruction. Although the theoretical and practical aspects of conflict management are converging, a void of considerable size still separates the two. The main cause of which is failure to address root causes. Under normal circumstances political intervention is ingrained on the implementation of appropriate and authoritative mandates. Protection of human rights and military or economic interests are part of the justifications for intervention. The rationale for intervention is to create (or the desire to initiate one) international society which holds fast to the international law through diplomacy in order to achieve balance of power. However, the idea of international society conflicts with the demand of absolute sovereignty by nations who favor complete political autonomy and the power to act or the quality of being an independent self-governing nation. There are two schools of thought in this regard: Pluralists who stick onto minimal rules for coexistence with non-interference in the domestic affairs of the state but allows alliance to deter or resist aggression. The other school, the Solidarists, advocates the idea that sovereignty depends on the full coexistence of international society. Decades of providing assistance to war ragged nations to resolve armed conflicts, suggests that international intervention has yet to produce effective and sustainable results and persistent threat of recurring armed conflict remains conspicuous. The aim of this paper is to investigate the meagerness of international intervention and its methodology. The central argument of this paper leads to the fact that current political crisis of the world has resulted from the dreadful collapse of political leadership in the international level.